Touch and translanguaging in a multilingual early childhood education setting. Issue 3 (September 2022) - Samuelsson, Robin
Many children grow up in multilingual communities characterised by linguistic heterogeneity and semiotic and cultural complexity. Translanguaging theory has provided a perspective attuned to communication and education in multilingual settings. However, translanguaging pedagogies have not yet had a broad uptake in early educational settings. The recent interest in embodiment within translanguaging studies and the study of touch combinedly provide a potential perspective for early childhood education. This study examines the role of touch in a multilingual preschool featuring 2-year-olds. The results point to two key functions for touch. One is that touch creates a shared experiential ground where languages can be learned. The other function is that touch allows children to sensorially explore and learn multicultural experiences from the diverse cultural and linguistic systems available. Based on the results, the role of touch in early childhood translanguaging is discussed as a way forward for translanguaging pedagogies for creating both equitable and diverse educational opportunities for children in multicultural and multilingual communities.